hey can anybody solve this question .... if f(x)=x2-x,show that f(x+1)=f(-x)

At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions.

A community for students.

hey can anybody solve this question .... if f(x)=x2-x,show that f(x+1)=f(-x)

Mathematics
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions

f(x+1) = (x+1)^2 - (x+1) = x^2 +2x +1 - x -1 =x^2 +x = f(-x)
f(x+1)=(x+1)^2 -(x+1) = (x+1)((x+1-1) = x(x-1)=f(x)...ur statement is wrong..maybe??
hey thanx mate

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

but iam still blank :S
nah ive checked it statement is right
ankur \[f(x)\neq x(x-1)\]
err nvm, durr
\[f(x)=x ^{2}-x\] This was given Show that f(x+1) = f(-x). Work out each one and see if it is true First do f(x+1)\[f(x+1)=(x+1)^{2}-(x+1)=x ^{2}+2x+1-x-1=x ^{2}+x\] Now work it out for -x \[f(-x)=(-x)^{2}-(-x)=x ^{2}+x\] The results look the same to me

Not the answer you are looking for?

Search for more explanations.

Ask your own question